Protection affects the abundance and activity patterns of pumas in the atlantic forest - Paviolo, Agustin Javier (2009)
Knowing the factors that affect the abundance and activity patterns of pumas (Puma concolor) in South American forests may help in their conservation. Using camera traps, we conducted 4 surveys in 3 areas with different levels of protection against poaching and logging within the biggest continuous fragment of the Upper Parana Atlantic Forest. We used capture-mark-recapture population models to estimate the density of pumas for each area. The core area of Iguazú National Park, with low poaching pressure and no logging for >60 years, had the highest density of pumas (between 1.55 and 2.89 individuals/100 km2). Yaboti Biosphere Reserve, an area with the highest poaching and logging pressure, showed the lowest density (between 0.3 and 0.74 individuals/100 km2). Areas with intermediate levels of poaching and logging pressure had densities between 0.66 and 2.19 individuals/100 km 2. Puma activity peaked during the 1st hours of morning in the most protected area, but became more crepuscular and nocturnal in areas with less protection. The lower abundance of pumas in the more degraded areas may be related to lower prey abundance. Differences in activity patterns of pumas among areas with different poaching pressures may be a direct response to poaching or to changes in the availability and activity patterns of primary prey. Conservation efforts should focus on decreasing poaching and logging pressures within protected areas to benefit pumas and other endangered species in the Atlantic Forest. © 2009 American Society of Mammalogists.